Customer interactions on social media and their impact on trust and loyalty: the moderating role of product learning - Ismet Esenyel; Mete Girgen (Management Science Letters, 2019)
This research examines the customer engagement on social media platforms in the tourism industry and its effect on customer loyalty through the mediated effect of customer trust. Furthermore, the moderating role of product learning is investigated on the hypothesized relationships. Data was collected from guests in 5 stars hotels in Kyrenia region in Northern Cyprus. In this study, out of the 459 collected surveys, only 419 were analyzed due to missing or incomplete data. The analysis conducted here followed the two step approach for structure equations modelling. Firstly, a confirmato-ry factor analysis was appraised to prepare data for structural model. Then the structural model helped shape our direct hypothesis testing, before analyzing the mediating and moderating impacts. The data provided evidence to link customer interactions on social media with trust and loyalty (Hypotheses 1-3) while trust revealed a mediating effect between interaction and loyalty. Finally, product learning did have an empowering impact on the relationship between interaction and trust.